Coping with Complexity Model Reduction and Data Analysis - Gorban, Alexander N.; Roose, Dirk.; SpringerLink (Online service). (Berkeley, Calif. Apress, 2011)
This volume contains the extended version of selected talks given at the international research workshop "Coping with Complexity: Model Reduction and Data Analysis", Ambleside, UK, August 31 September 4, 2009. The book is deliberately broad in scope and aims at promoting new ideas and methodological perspectives. The topics of the chapters range from theoretical analysis of complex and multiscale mathematical models to applications in e.g., fluid dynamics and chemical kinetics.
Electronic reproduction.
Keywords: Mathematics; Chemical engineering; Systems theory